1964
DOI: 10.2307/1933835
|View full text |Cite
|
Sign up to set email alerts
|

Shallow-Water Marine Climates and Molluscan Provinces

Abstract: Definitions of shallow—water marine climatic zones that equate the northern limit of climatic zones with minimum temperatures are shown to be not critical. The critical factor that probably determines the limits of marine shallow—water climates is the number of consecutive days or months that shallow sea water is at temperatures required for reproduction and early growth. The relations that appear to exist between duration of marine water temperature or climate and molluscan provinces are: (1) Inner tropical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

1965
1965
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 12 publications
7
76
0
1
Order By: Relevance
“…Instead, Hall (1964) suggested that the number of consecutive days in summer when shallow water temperatures are warm enough for spawning and larval activity is critical. Bernard et al (1991) found a strong positive correlation between mean annual surface temperatures and the number of intertidal bivalve species in the northeast Pacific.…”
Section: Molluscan Zonesmentioning
confidence: 99%
“…Instead, Hall (1964) suggested that the number of consecutive days in summer when shallow water temperatures are warm enough for spawning and larval activity is critical. Bernard et al (1991) found a strong positive correlation between mean annual surface temperatures and the number of intertidal bivalve species in the northeast Pacific.…”
Section: Molluscan Zonesmentioning
confidence: 99%
“…Provincial boundaries are located where waters of different major water masses or water types, conditioned in different climatic zones or representing mixtures of waters drawn from other distinctive sources, and distributed by currents, meet along the shelf (for example Dall 1921, Schenck & Keen 1936, Hall 1964, Valentine 1966, Gaylord & Gaines 2000. Previous studies have shown that provincial boundaries, formed by clusters of species-range endpoints, influence many aspects of northeastern Pacific molluscan biogeography (Roy et al 1994(Roy et al , 1998, and the finding that the geographic ranges of carnivores and non-carnivores are different and vary regionally raises the possibility that they are associated with similar features.…”
Section: Zonal Controlsmentioning
confidence: 99%
“…These two coastline stretches are unique in having the widest temperature range. Each contains signi cant provincial boundaries (Hall, 1964;Valentine, 1966). The in uence of the large temperature range on parasite distributional pattern potentially minimizes the possibility that correlations with contaminants can be identi ed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%